The economisation of social policy and the rise of a crisis-prone culture - Kananen, Johannes (Faculty of Political Science and International Studies, University of Warsaw, 2025)
The economisation of social policy implied the emergence of neoclassical economics as a contestant for the foundation of social policy in theory and practice. A crucial phase in this process is the emergence of the international competition state paradigm, which urges governments to cut taxes, reduce generosity and tighten eligibility criteria for social security benefits. The adoption of the competition state paradigm reversed social policy in advanced welfare states, which used to balance the injustices of capitalism through an expansion of social citizenship rights. In Nordic welfare states, such as Denmark and Finland the advance of the competition state paradigm resulted in a clash with the constitution, which seeks to guarantee a minimum standard of living for all citizens. The economisation and subsequent reversal of the purpose of social policy was followed by increasing social inequality and a more general development characterised by a series of crises in the areas of economy, health, politics, environment, security, and global mobility. A seed of this development is endogenous, or internal, in other words, and lies in the representation of the human being associated with neoclassical economics and the competition state paradigm, according to which the pleasure-seeking human being is a potential free-rider and lazy idler in need of subordination and control. The article distinguishes between exogenous (or external) and endogenous (or internal) aspects of welfare state change and highlights our role as citizens and academics in both creating and resolving challenges related to societal development.